MODEL PEMBELAJARAN QUANTUM LEARNING DENGAN MEDIA SQUARE BOARD TERHADAP HASIL BELAJAR SISWA PADA MATERI SEGIEMPAT - Rosalia Octaviani; Endang Suprapti; Achmad Hidayatullah (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2020)
This research aims to determine the effect of Square Board Media with Quantum Learning model on learning outcomes, student and teacher activities and student responses in class VII-D students of Muhammadiyah 2 Junior High School Surabaya. This research is a type of quantitative research with the True Experimental method. The design used in this study is Pretest-Posttest Control Group Design. Samples taken were 52 students consisting of 26 experimental class students and 26 control class students. The results showed that the average final test score in the experimental class was better than the average test final score in the class control; (2) The most dominant student activity occurs is the activity of students